Enhanced levitation force of partial melted (Y,Er)Ba2Cu3O7-8 superconductors with formation of minor 211 phase / Ahmad Kamal Yahya, Suzi Ahmad and Imad Hamadneh - Yahya, Ahmad Kamal; Ahmad, Suzi; Hamadneh, Imad (Faculty of Applied Sciences, 2005)
Y0.5 Er 0.5 Ba2 Cu307-8 superconductors with Er2 O3 addition were prepared by partial melting and the effects of excess Er2 03 addition on the magnetic levitation force (MLF) of the partial-melted samples have been investigated. A non-linear relationship was observed between the MLF measured at 77 K and the amount of Er2 O3. It was found that the optimum amount of excess Er2 O3 for enhanced MLF is 10 wt.%. X-ray powder diffraction analysis showed formation of major 123 phase with minor 211 non-superconducting phase for all samples. The results were discussed in detail and the presence of 211 impurities is suggested to act as pinning centers in the 123 samples.